2010
DOI: 10.1021/nn1018208
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Dot Sensitized Solar Cells with Improved Efficiency Prepared Using Electrophoretic Deposition

Abstract: Quantum dot sensitized solar cells (QDSSC) may benefit from the ability to tune the quantum dot optical properties and band gap through the manipulation of their size and composition. Moreover, the inorganic nanocrystals may provide increased stability compared to organic sensitizers. We report the facile fabrication of QDSSC by electrophoretic deposition of CdSe QDs onto conducting electrodes coated with mesoporous TiO(2). Unlike prior chemical linker-based methods, no pretreatment of the TiO(2) was needed, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
199
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 249 publications
(204 citation statements)
references
References 54 publications
4
199
0
1
Order By: Relevance
“…QDs were deposited on both the cathode and anode electrodes similar to previous reports. 18 Fresh layers at each deposition time were taken from the electrophoretic cell, rinsed several times with toluene to wash off unbound QDs, subsequently rinsed with ethanol, and dried at room temperature. After electrophoretic deposition colloidal QDs were coated with a CdS layer grown by SILAR.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…QDs were deposited on both the cathode and anode electrodes similar to previous reports. 18 Fresh layers at each deposition time were taken from the electrophoretic cell, rinsed several times with toluene to wash off unbound QDs, subsequently rinsed with ethanol, and dried at room temperature. After electrophoretic deposition colloidal QDs were coated with a CdS layer grown by SILAR.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Performing ligand exchanges, where the original lengthy ligands are substituted for shorter bifunctional ligands, has improved CQD loading due to the enhanced anchoring of CQDs to the titania electrode [160,161]. Alternative loading methods, including a pressing technique [162] and electrophoretic deposition [163], have led to improved CQD loading and elimination of regions exposed to the redox electrolyte. In recent studies, pH control was demonstrated to increase quantum dot loading as well as reduce interfacial recombination in CQD-SSC devices [164,165].…”
Section: Cqd-sensitized Photovoltaicsmentioning
confidence: 99%
“…Adaptive mesh refinement was utilized over the course of the simulation to increase mesh density near large gradients in volume fraction. The solution to (8) was found using the built-in electrostatics module, while (9) was implemented as a generic PDE. Time stepping was performed using the BDF method with a MUMPS solver.…”
Section: Performing the Simulationsmentioning
confidence: 99%